60GHz Reverse Modulation Fiber-Wireless System with Two Jointed DSP Algorithms - Long Chen; Ziwei He; Lv Zhao; Bin Zhong (Advances in Condensed Matter Physics)
In this paper, we propose a reverse modulation fiber-wireless system with two jointed DSP algorithms. The signal in the system is OFDM modulated millimeter wave (mm-wave) at 60GHz. In order to improve transmission of this system, the discrete Fourier transform spread (DFT-Spread) technology and the averaging of the channel frequency response (H-averaging) technology are applied. The DFT-Spread technology helps to reduce the peak-to-average power ratio (PAPR) of the OFDM signal, and the H-averaging technology helps to optimize channel estimation. This is the first time that the two kinds of technology were used together in this reverse modulation system. According to the simulation, the 22Gbit/s 16QAM-OFDM at 60GHz can be generated and transmitted for 90km fiber transmission under the soft decision forward error correction (SD-FEC) threshold 3.8×10-3. The results show that the two jointed DSP algorithms can improve the reverse modulation system transmission performance obviously.